2020
DOI: 10.3390/cancers12071847
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of MET and PD-L1 Expression in Malignant Melanoma

Abstract: The proto-oncogene MET, the hepatocyte growth factor (HGF) receptor, is a transmembrane receptor tyrosine kinase (RTK) with a prominent role in tumor metastasis and resistance to anti-cancer therapies. Melanoma demonstrates relatively frequent MET aberrations, including MET gene amplification. Concurrently, programmed death-ligand 1 (PD-L1), with its ability to evade anti-tumor immune responses, has emerged as a prominent therapeutic target in melanoma and other malignancies and its expression is used … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Our patient’s melanoma had an NRAS mutation where MEK inhibitors may have a role as systemic therapy, although a modest and short-lived responses are generally expected based on the experience with metastatic cutaneous melanoma. Furthermore, MET aberrations have been frequently demonstrated in melanoma and an interplay between MET and PD-L1 expression has been reported in cutaneous and mucosal melanoma ( 22 ), supporting experimental strategies involving combinatorial approaches of MET inhibition and immunotherapy that may have a role in this disease ( 23 ).…”
Section: Discussionmentioning
confidence: 92%
“…Our patient’s melanoma had an NRAS mutation where MEK inhibitors may have a role as systemic therapy, although a modest and short-lived responses are generally expected based on the experience with metastatic cutaneous melanoma. Furthermore, MET aberrations have been frequently demonstrated in melanoma and an interplay between MET and PD-L1 expression has been reported in cutaneous and mucosal melanoma ( 22 ), supporting experimental strategies involving combinatorial approaches of MET inhibition and immunotherapy that may have a role in this disease ( 23 ).…”
Section: Discussionmentioning
confidence: 92%
“…Prior studies using melanoma cell lines or patient FFPE tissue demonstrated a wide range of MET expression in both nevi and melanomas. There is a significantly higher proportion and expression level in melanomas than in nevi, while the expression levels are comparable in primary and metastatic melanomas ( 3 , 20 ). MET expression data in our study is consistent with prior studies in the literature.…”
Section: Discussionmentioning
confidence: 96%
“…Our findings are consistent with their conclusions as the pooled HRs of survival data concerning VEGFR overexpression are relatively higher than other RTKs. Hepatocyte growth factor receptor (cmesenchymal-epithelial transition factor, c-Met) is a transmembrane protein encoded by the Mesenchymalepithelial transition factor (Met) gene, which is usually abnormally expressed in melanoma due to increased copy number, exon skipping, and gene mutations (19,44). Several studies also found that c-MET may represent a potential biomarker and therapeutic target for melanoma, which warrants further exploration (45,46).…”
Section: Discussionmentioning
confidence: 99%